2008
DOI: 10.1636/st07-66.1
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic changes in web architecture and growth rate of Tengella radiata (Araneae, Tengellidae)

Abstract: In some spiders features of the webs of early instars may represent features of the ancestor's web. Some second instar spiderlings (first instar outside of the egg sac) of Tengella radiata (Kulczynski 1909) construct a small sheet web without any type of retreat. In subsequent instars, spiderlings construct webs that consist of a sheet with a small retreat that opens near its center. Webs gradually change as spiderlings growth and webs of 7 th instar spiders are indistinguishable from those of adult females. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 8 publications
3
26
0
1
Order By: Relevance
“…The lack of significant correlation between predictor and response variables may be due to second instars being more similar. Many spiders start out with the same general number of spigots upon emergence from the egg sac (second instar) and differentiation between foraging strategies may not be apparent at this instar, e.g., some second instar web builders do not spin webs (Table S1, Manuscript to be reviewed Hajer et al, 1991;Barrantes & Madrigal-Brenes, 2008;R.E. Alfaro, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of significant correlation between predictor and response variables may be due to second instars being more similar. Many spiders start out with the same general number of spigots upon emergence from the egg sac (second instar) and differentiation between foraging strategies may not be apparent at this instar, e.g., some second instar web builders do not spin webs (Table S1, Manuscript to be reviewed Hajer et al, 1991;Barrantes & Madrigal-Brenes, 2008;R.E. Alfaro, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies of silk evolution have used web ontogeny as a tool to reconstruct ancestral web conditions or plesiomorphic traits in silk use. Studies many from to the Araneoidea (Robinson & Lubin, 1979;Eberhard, 1985;Eberhard, 1986;Barrantes & Madrigal-Brenes, 2008; Barrantes & Eberhard, 2010), suggested that early instar webs and behavior resembled possible ancestral states. In studies of both Tengella perfuga F. Dahl (1901) and Tengella radiata (W. Kulczyński, 1909), early instar webs resembled simple sheet webs rather than the complex funnel structures lined with cribellate silk observed in adults (Barrantes & Madrigal-Brenes, 2008;Mallis & Miller, 2017).…”
mentioning
confidence: 99%
“…For instance, the length of the proximal segments (e.g., femur and tibia) of the pedipalp of males in some spider species physically determines the male capability of reaching the female copulatory opening (Barrantes & Ramírez, 2013), and to reduce predation risk if longer pedipalps allow males to remain further away from aggressive females (Anderson & Hebets, 2016;Barrantes & Madrigal-Brenes, 2008). The rationale for this hypothesis is that in a sexual context the length of reaching structures could limit males to reach the female copulatory opening and thus reduce their probability to transfer spermatozoids successfully.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, small males would benefit from possessing proportionally longer structures than large males, resulting in a negative allometric relationship. For instance, the length of the proximal segments (e.g., femur and tibia) of the pedipalp of males in some spider species physically determines the male capability of reaching the female copulatory opening (Barrantes & Ramírez, 2013), and to reduce predation risk if longer pedipalps allow males to remain further away from aggressive females (Anderson & Hebets, 2016;Barrantes & Madrigal-Brenes, 2008). The allometric prediction for reaching structures is likely species-specific, because the particular features of these structures are expected to be influenced by the size and courtship behavior of each species Barrantes, Sánchez-Quirós, Aisenberg, Leitch, & Eberhard, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Ontogenetic studies of silk spinning apparatuses in spiders could reveal additional information on the ancestral traits and silk use behaviors, much like web ontogeny studies illuminated web evolution. For decades, these kinds of studies have been suggested (Peters ; Eberhard , ; Barrantes & Madrigal‐Brenes ; Barrantes & Eberhard ; Mallis & Miller ). Prior to this study, there were no published datasets on the ontogeny of the full spinning apparatus of a cribellate spider.…”
mentioning
confidence: 99%